Chicken interferon regulatory factor 1 (IRF1) involved in antiviral innate immunity via regulating IFN-β production. (November 2018) - Liu, Yunxia; Cheng, Yuqiang; Shan, Wenya; Ma, Jingjiao; Wang, Hengan; Sun, Jianhe; Yan, Yaxian
Abstract: Interferon regulatory factors (IRFs) is an important family for IFN expression regulating while viral infection. IRF1, IRF3, and IRF7 are the primary regulators that trigger type I IFN response in mammals. However, IRF3, which has been identified as the most critical regulator in mammals, is absent in chickens, and it is unknown whether IRF1 is involved in type I IFN signaling pathways in IRF3-deﬁcient chicken cells. Here, we identified chicken IRF1 (chIRF1) as a critical IFN-β mediator in response to viral infection. Overexpression of chIRF1 activated IFN-β intensively and suppressed AIV and NDV viral replication. Moreover, the mRNA levels of IFN-β and ISGs increased during chIRF1 overexpression. In addition, deletion mutant analysis revealed that the first four domains of chIRF1 are indispensable for IFN-β induction. Together, our studies demonstrate that chIRF1 is an important regulator of IFN-β and is involved in chicken antiviral innate immunity. Highlights: ChIRF1 is an important regulator of IFN-β signaling in IRF3-null chicken cells. The essential domain of chIRF1 for IFN-β induction was identified. ChIRF1 is involved in antiviral innate immunity.